Il ruolo dell’Ufficio Cartografico Regionale per la conoscenza del territorio - Tabarrani, Ilaria (GEOmedia, 2024)
Administrative action must base decisions on certified georeferenced cognitive elements because errors and inaccuracies can affect public decision-making. With this in mind, the Tuscany Region's overall strategy is one that includes, in addition to the implementation of remote sensing data, improving the quality of spatial data produced as part of the administrative functions under its jurisdiction. To do this, the Region renews the role of its Cartographic Office, recognizing its variable geometry but placing it at the center of the complex coordination system for the certified acquisition of georeferenced information.